2005
DOI: 10.1111/j.1463-6409.2005.00188.x
|View full text |Cite
|
Sign up to set email alerts
|

A new cryptic species of pond turtle from southern Italy, the hottest spot in the range of the genus Emys (Reptilia, Testudines, Emydidae)

Abstract: 2005). A new cryptic species of pond turtle from southern Italy, the hottest spot in the range of the genus Emys (Reptilia, Testudines, Emydidae). -Zoologica Scripta , 34 , 351-371. Geographic variation in the mtDNA haplotypes (cytochrome b gene) of 127 European pond turtles from Italy was investigated. Thirty-eight of the Italian samples were also studied by nuclear fingerprinting (ISSR PCR) and compared with samples from other parts of the range representing all nine currently known mtDNA lineages of Emys or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
168
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 109 publications
(181 citation statements)
references
References 25 publications
12
168
0
1
Order By: Relevance
“…Although the presence of usual phylogeographic breaks does not exclude co-differentiation between Heligmosomoides and its host, co-differentiation might not be the most likely cause of these interruptions. In contrast, other phylogeographic breaks shared by Heligmosomoides and A. sylvaticus in South Western Europe do not correspond to phylogeographic breaks typically found in many other taxa: i.e., the differentiation of Sicily from continental Italy (even if few studies showed that Sicily is a hotspot of biodiversity in Europe (Randi et al, 2003;Fineschi et al, 2005;Fritz et al, 2005)), and the differentiation of Maghreb populations from Spain. These shared specific phylogeographic breaks are, in contrast to usual phylogeographic fractures, good clues arguing for long-term co-differentiation between the two species (Thompson, 2005).…”
Section: Regional Co-differentiation Between Heligmosomoides and A Smentioning
confidence: 69%
“…Although the presence of usual phylogeographic breaks does not exclude co-differentiation between Heligmosomoides and its host, co-differentiation might not be the most likely cause of these interruptions. In contrast, other phylogeographic breaks shared by Heligmosomoides and A. sylvaticus in South Western Europe do not correspond to phylogeographic breaks typically found in many other taxa: i.e., the differentiation of Sicily from continental Italy (even if few studies showed that Sicily is a hotspot of biodiversity in Europe (Randi et al, 2003;Fineschi et al, 2005;Fritz et al, 2005)), and the differentiation of Maghreb populations from Spain. These shared specific phylogeographic breaks are, in contrast to usual phylogeographic fractures, good clues arguing for long-term co-differentiation between the two species (Thompson, 2005).…”
Section: Regional Co-differentiation Between Heligmosomoides and A Smentioning
confidence: 69%
“…In our freshwater turtle model, we found that the SSD pattern was differently expressed according to groups and localities (see Figures 2-4). This highlights the presence of different morphological body size architectures (Fritz 1995;Zuffi & Ballasina 1998), and may also confirm some of the differences found at the genetic level (Lenk et al 1998(Lenk et al , 1999Fritz et al 2005). In fact, the significant body size differences among populations of the Eastern Po Plain, the Tyrrhenian coast, Sicily, Corsica and Sardinia support, at least at a certain degree, most previous morphological data (Fritz 1995(Fritz , 1998Fritz & Obst 1995;Zuffi & Gariboldi 1995a;Zuffi & Ballasina 1998;Fritz 2003) that described different subspecies.…”
Section: Discussionmentioning
confidence: 69%
“…In Corsica and Sardinia two other subspecies were described on the basis of morphological peculiarities: E. o. lanzai, and E. o. capolongoi. All these subspecies are characterised by the same mitochondrial haplotype (Lenk et al 1999), while the Sicilian taxon has been found to show a markedly different mitochondrial pattern (Fritz et al 2005).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations